Industrial and Biotechnological Applications of Algae: A Review - Poonam, Sharma; Nivedita, Sharma (Journal of Advances in Plant Biology, 2017)
Algae are a class of photosynthetic organisms found in both marine and freshwaters habitats. As these organisms have a short doubling time, they are considered among fastest growing creatures. They have different pathways to fix atmospheric carbon dioxide and to efficiently utilize the nutrients to convert it into biomass. In few years, a focus has been shifted towards these organisms due to their food and fuel production capability. In fuel industry algae biofuels have been emerged as a clean, nature friendly, cost effective solution to other fuels. Algae fuels are categorized into bio-ethanol, biogas, bio-hydrogen, biodiesel and bio-oil. Algae as a food have been explored for different applications as in production of single cell proteins, pigments, bioactive substances, pharmaceuticals and cosmetics. The present review has been prepared to throw a light on enormous applications of algae as food and fuel and also to provide some information about different commercially available algae products.
Keywords: Algae; Microalgae; Macroalgae; Biofuel; commercial; Potential